2018
DOI: 10.1016/j.jpainsymman.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Palliative Care Needs Among Patients With End-Stage Kidney Disease: A National Registry Study About the Last Week of Life

Abstract: Even if death is expected, most patients dying with ESKD had unmet palliative care needs regarding symptom management, advance care planning, and bereavement support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
2
26
0
6
Order By: Relevance
“…In accordance with earlier studies from the SRCP, examining other diagnoses and specific types of care, the prevalence of symptoms was high during the last week of life (Andersson, Årestedt, Lindqvist, Fürst, & Brännström, ; Årestedt et al, ; Axelsson et al, ; Smedbäck et al, ). It is not surprising that, for example, shortness of breath and rattles were common symptoms in MND, since the major direct causes of death are pneumonia and respiratory failure (Cheng et al, ; Gil et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with earlier studies from the SRCP, examining other diagnoses and specific types of care, the prevalence of symptoms was high during the last week of life (Andersson, Årestedt, Lindqvist, Fürst, & Brännström, ; Årestedt et al, ; Axelsson et al, ; Smedbäck et al, ). It is not surprising that, for example, shortness of breath and rattles were common symptoms in MND, since the major direct causes of death are pneumonia and respiratory failure (Cheng et al, ; Gil et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Only around 32% of the patients with OND were offered end‐of‐life discussions, while the figure was around 69% in the case of their family members. It may be that these numbers are related to cognitive or consciousness decline and similar results are found for other diagnoses (Årestedt et al, ; Axelsson et al, ). It would be interesting to explore why patients do not receive this discussion.…”
Section: Discussionsupporting
confidence: 62%
“…In both the univariate and multiple logistic regressions, the use of a validated pain symptom assessment scale was significantly associated with relief of pain, nausea, anxiety, and shortness of breath. Despite this, recent studies have shown that symptom assessment scales are seldom used in dying patients with end-stage kidney disease 28 and heart failure. 29 One explanation could be that persons at EOL may have restricted verbal communication, making it hard for them to express their needs.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers of urea, creatinine, hemoglobin, hematocrit, albumin, sodium, potassium, calcium, phosphorus, and C-reactive protein (CRP) values of the subjects who participate in the study were evaluated. The median number of medications used by the patients on a daily basis was three (min-max: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Normally deviating values were determined and the relationship between the HSS, HSS subscales, TAS-20, and TAS-20 subscale scores was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…14 It is not appropriate to handle symptom management or the psychosocial dimension of CRF solely through a nursing approach. 15 Therefore, a nurse has to adopt a holistic approach while performing care activities during CRF and hemodialysis treatment.…”
mentioning
confidence: 99%